2003
DOI: 10.1038/sj.bdj.4810821
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reactions to protective gloves used in the dental profession: experience of the UK Adverse Reaction Reporting Project

Abstract: The Adverse Reaction Reporting Project (ARRP) was set up to measure the extent and severity of adverse reactions to dental materials in the UK. Further analysis into the use of protective gloves has been carried out to establish the degree to which gloves are having a deleterious effect on the dental profession. In addition the survey aimed to establish the techniques used to manage adverse reactions and their effectiveness. In a 23-month period, 369 reports were received concerning adverse reactions to protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
(24 reference statements)
0
17
0
Order By: Relevance
“…Subsequent research showed a decline in the incidence from 8.5% to 4.3%, which was related to using latex gloves of better quality with lesser amounts of allergens 7,21,27,28 . A study performed in Great Britain on the side eff ects of latex gloves among dentists revealed that the majority of allergies to latex could be controlled by self-medication, prescribed therapy and/or changing to other types of gloves 29 . Successful preventive programs were also introduced in order to decrease the incidence of allergies to latex or other dental materials (i.e.…”
Section: Reactions To Latexmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent research showed a decline in the incidence from 8.5% to 4.3%, which was related to using latex gloves of better quality with lesser amounts of allergens 7,21,27,28 . A study performed in Great Britain on the side eff ects of latex gloves among dentists revealed that the majority of allergies to latex could be controlled by self-medication, prescribed therapy and/or changing to other types of gloves 29 . Successful preventive programs were also introduced in order to decrease the incidence of allergies to latex or other dental materials (i.e.…”
Section: Reactions To Latexmentioning
confidence: 99%
“…For some people with CD, it is possible to wear latex gloves that do not contain other chemicals. Furthermore, frequent hand washing after the use of gloves is recommended, as well as the usage of appropriate skin care (hydrating creams or ointments), while for periods of worsening, topical corticosteroids and sometimes systemic antihistamines are usually applied 19,29 . In some countries, local state authorities participate in the prevention of these disorders through regulatory actions that reduce the risk of latex products in health workers and patients.…”
Section: Reactions To Latexmentioning
confidence: 99%
“…Further analyses by the ARRP into glove related adverse reactions have been carried out and forms the basis of a separate article in the British Dental Journal. 15 The degree of reactions reported was mainly moderate (n = 469: 44%) however most of these reports did not always follow closely to the ARRP guidelines, mainly through a lack of referring the affected person to a specialist for diagnosis which is a prerequisite of the ARRP moderate reaction type definition. When the figures were revised to follow the guidelines, 43% were mild (n = 457), 30% moderate (n = 324) and 12% severe (n =126).…”
Section: Discussionmentioning
confidence: 99%
“…27 If this step is unsuccessful, they should change to non-latex gloves or should wear glove liners under their latex gloves. 28 Additionally, washing the hands frequently after the use of gloves could help remove irritants causing allergy. 27 Dentists with known NRL protein hypersensitivity should use only non-latex (nitrile) gloves and should undertake proper hand care in the form of topical moisturizers and corticosteroid-or antihistaminecontaining ointments, which is why the usage of nitrile gloves is the most important preventive measure in the dental occupation.…”
Section: Discussionmentioning
confidence: 99%
“…27 Dentists with known NRL protein hypersensitivity should use only non-latex (nitrile) gloves and should undertake proper hand care in the form of topical moisturizers and corticosteroid-or antihistaminecontaining ointments, which is why the usage of nitrile gloves is the most important preventive measure in the dental occupation. 17,28 To prevent hand eczema caused by methyl methacrylates, it is important to develop no-touch techniques to avoid skin exposure to these chemicals. 29 Additionally, protection can be improved using nitrile rubber gloves or double gloving to prevent small molecular acrylates from permeating the gloves;in this manner, direct skin contact could be avoided.…”
Section: Discussionmentioning
confidence: 99%